Creating an EU-level supervisor for cross-border banking groups: Issues raised by the U.S. experience with dual banking - Larry D. Wall; María J. Nieto; David Mayes (Federal Reserve Bank of Atlanta, 2011)
The European Union (EU) has been facilitating the growth of cross-border banking groups, but bank supervision remains the responsibility of national supervisors. This mismatch has long been recognized and various proposals have been offered to address this weakness. An alternative that would retain the most important advantages of full centralization is that of centralization only for those cross-border groups that are systemically important. All other banks would remain national responsibilities. To identify some of the issues (but not necessarily the best answers) raised by partial centralization in the EU, we look to the dual banking arrangements in the United States, which has long had both federal and state charters. One issue is that of who qualifies for and/or is required to adopt an EU charter. The U.S. policy of low-cost chartering changes encourages both good and bad competition among supervisors. A second issue is that of the potential mismatch between EU responsibility for prudential supervision of some banks and national provision of deposit insurance and lender of last resort services for all banks. A third potential issue is who should provide business conduct regulation.
Keywords: G28; F36; K23; 330; cross-border banking